2010
DOI: 10.1007/978-3-642-15234-4_28
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating and Learning Predators on a Pursuit Scenario

Abstract: Abstract.A generic predator/prey pursuit scenario is used to validate a common learning approach using Wilson's eXtended Learning Classifier System (XCS). The predators, having only local information, should independently learn and act while at the same time they are urged to collaborate and to capture the prey. Since learning from scratch is often a time consuming process, the common learning approach, as investigated here, is compared to an individual learning approach of selfish learning agents. A special f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Many multiagent research efforts utilize the original discretized predator-prey pursuit environment shown in Figure 1, implementing a toroidal grid world and requiring the single prey to be blocked on all sides by four predators [7,21,22]. These studies tend to focus less on the structure of the environment and more on how specific sets of predator strategies impact cooperation and teamwork in homogenous and heterogeneous groups of predators.…”
Section: Modifications To the Predator-prey Pursuit Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Many multiagent research efforts utilize the original discretized predator-prey pursuit environment shown in Figure 1, implementing a toroidal grid world and requiring the single prey to be blocked on all sides by four predators [7,21,22]. These studies tend to focus less on the structure of the environment and more on how specific sets of predator strategies impact cooperation and teamwork in homogenous and heterogeneous groups of predators.…”
Section: Modifications To the Predator-prey Pursuit Environmentmentioning
confidence: 99%
“…Some research allows the agents to be omniscient, where all entities' positions are known at every time point [17,35], whereas other studies permit agents to see in a straight line until an occlusion is encountered [33,[38][39][40]. Some allow predators and prey to see only within a given range around themselves [21,30,41] or apply random limitations to predator vision [42]. While some research explores predators with limited sensing abilities, these studies allow information to be shared among predators [21,36], either through direct communication (e.g., police radio, [36]) or indirectly (e.g., by leaving cues such as pheromone trails in the environment) [26].…”
Section: Changes In Agent Capabilitiesmentioning
confidence: 99%
See 3 more Smart Citations